Clinical Practice of Treating Benzodiazepine Poisoning with Kahwa (Black Tea) in Acute Cases of Overdose: Benzodiazepine Poisoning with Kahwa (Black Tea) in Acute Cases of Overdose - Khan, Javeria; Khan, Muhammad Inam; Khan, Muhammad Ashar; Sultan, Omer; Khan, Amnah; Zahra, Desaar (Pakistan Journal of Health Sciences, 2026)
Recently, an increasing trend of using black tea (Kahwa) in many diseases has been noticed due to its numerous health benefits with less to no side effects and easy availability. Objectives: To describe the clinical characteristics, management practices, and short-term outcomes of patients with acute benzodiazepine overdose who received Kahwa as part of supportive care. Methods: This retrospective descriptive study was conducted at the National Poison Control Center, Jinnah Postgraduate Medical Center, Karachi. Patients aged 13–70 years with confirmed acute benzodiazepine overdose were included using a non-probability consecutive sampling technique. All patients received standard supportive care plus enteral feeding of Kahwa via nasogastric tube (NG). Data were analyzed using IBM-SPSS version 26.0, and significance was set at p<0.05. Results: A total of 200 patients with acute benzodiazepine overdose were analyzed. There were 50.5% patients who were male, with an overall median age of 24 years (IQR: 20–38). In most cases, 75.5% presented within two hours of ingestion, and 81.5% had taken ten or fewer tablets. Hypertension and diabetes were present in 4.5% and 4.0% of patients, respectively. The most common presenting features were altered consciousness (25.0%) and non-reactive pupils (27.5%). Intubation was required in 2 patients (1.0%), and flumazenil was given to 3 (1.5%). Conclusions: This study documents current clinical practice in managing benzodiazepine overdose, including adjunctive Kahwa administration. The results are descriptive and do not indicate the therapeutic effect of Kahwa specifically, as no causal interpretation is possible.